2016
DOI: 10.14260/jemds/2016/1011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Gestational Diabetes Mellitus: Insulin or Metformin?

Abstract: BACKGROUNDMetformin has established as an ideal first-line treatment for type 2 diabetes and hypothetically a particularly attractive drug for use in pregnancy. Metformin is known to cross the placenta and its use in pregnancy has been limited by concerns regarding potential adverse effects on both the mother and the foetus. Randomised trials to assess the efficacy and safety of its use for Gestational Diabetes Mellitus (GDM) are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In an RCT by Somani et al with no differences in glycemic outcomes between the metformin and insulin groups at baseline, higher PPG levels were reported in group treated with insulin compared to those treated with metformin ( p = 0.005) [ 26 ]. In an RCT by Ji et al with mixed population, a significant improvement in PPG and time in range (TIR) was observed with insulin detemir compared to insulin neutral protamine Hagedorn (NPH) ( p < 0.001) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an RCT by Somani et al with no differences in glycemic outcomes between the metformin and insulin groups at baseline, higher PPG levels were reported in group treated with insulin compared to those treated with metformin ( p = 0.005) [ 26 ]. In an RCT by Ji et al with mixed population, a significant improvement in PPG and time in range (TIR) was observed with insulin detemir compared to insulin neutral protamine Hagedorn (NPH) ( p < 0.001) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most included trials reported no difference in the proportion of cesarean sections among women treated with metformin versus insulin [ 21 , 24 , 26 , 33 39 ]. However, two RCTs by Galal et al and Hassan et al reported a significantly higher rate ( p ≤ 0.05) of cesarean sections in the insulin-treated group [ 20 , 40 ], while an RCT by Ijas et al reported a lower rate of cesarean section in the insulin-treated group versus metformin ( p = 0.047) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations